The Impact of Globalization on Hindu Religious Practices and Cultural Expressions - Andari, Ida Ayu Made Yuni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study investigates the impact of globalization on Hindu religious practices and cultural expressions through a comprehensive literature review. Utilizing a qualitative approach, the research integrates multiple dimensions of globalization’s influence, including the adaptation of religious rituals, transformation of artistic expressions, technological integration, changes in community structures, and dynamics of cultural identity. Data were systematically collected and analyzed using the Miles and Huberman model, ensuring a holistic understanding of how Hindu communities navigate the challenges and opportunities presented by globalization. The findings reveal that Hindu communities are increasingly incorporating modern elements into traditional rituals, such as the use of social media and digital platforms for disseminating teachings and conducting virtual rituals, thereby attracting younger generations and expanding their religious outreach. Additionally, contemporary Hindu art that blends traditional and modern elements exemplifies a creative response to global influences. The integration of digital technology enhances participation and facilitates the broader preservation and dissemination of Hindu culture. Changes in community structures, particularly due to migration and diaspora, highlight the evolving dynamics of cultural identity and adaptation to multicultural environments. This study addresses existing gaps by providing a holistic analysis that combines local wisdom with global dynamics, emphasizing the crucial role of character-based educational leadership in managing these changes. The research contributes theoretically by offering a new analytical framework and practically by providing strategies for cultural adaptation and preservation, thereby guiding Hindu communities in maintaining their identities in the global era.